A comparative in situ decomposition study using still born piglets and leaf litter from a deciduous forest. (July 2017) - Olakanye, Ayodeji O.; Nelson, Andrew; Ralebitso-Senior, T. Komang
Highlights: Compared 16S rRNA gene dynamics during pig and Quercus robur litter decomposition. Bacterial community shifts were more pronounced during summer interval. Potential to use Methylococcaceae as seasonal bacteria decomposition indicators. Methylophilaceae and Anaerolineaceae were potential microbial clock indicators for pig and leaf litter, respectively. Abstract: A cadaver and dead plant organic matter, or litter, are rich energy sources that undergo a complex decomposition process, which impact the surrounding environmental microbiota. Advances in molecular microbiology techniques, with study of the 16S RNA genes, in particular, have highlighted the application of forensic ecogenomics in addressing key knowledge gaps. To investigate subsurface microbiome shifts as a novel tool to establish "postmortem microbial clock" and augment postmortem interval (PMI) and time-since-burial estimations, an in situ study with triplicate underground burials of piglets as human taphonomic proxies and Quercus robur leaf litter was monitored for 270 days. Changes in microbial community structure and composition were related directly to changes in seasonal temperature, with microbial shifts more pronounced during the summer. For example, Methylococcaceae could be used as seasonal bacterial indicators, from winter to summer, in establishing postmortem microbial clock for this site. Furthermore, Methylophilaceae (Methylophilales order) and Anaerolineaceae would differentiate for the piglet and leaf litter soils, respectively, 180 days after internment.